2001
DOI: 10.1021/es001511o
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Arsenic Sequential Extraction Method for Evaluating Mobility in Sediments

Abstract: Arsenic (As) mobility and transport in the environment are strongly influenced by arsenic's associations with solid phases in soil and sediment. We have tested a sequential extraction procedure intended to differentiate the following pools of solid phase arsenic: loosely and strongly adsorbed As; As coprecipitated with metal oxides or amorphous monosulfides; As coprecipitated with crystalline iron (oxyhydr)oxides; As oxides; As coprecipitated with pyrite; and As sulfides. Additions of As-bearing phases to wetl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
241
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 481 publications
(250 citation statements)
references
References 38 publications
(44 reference statements)
8
241
0
1
Order By: Relevance
“…No sulfide phases, either arsenic or iron, were detectable in bulk sediments with powder XRD (36). Sequential extraction of arsenic and iron from sediments using an extraction scheme optimized for arsenic (42) showed that arsenic is not dominantly associated with easily exchanged sorption sites or with reducible iron (36). This finding indicates that much of the arsenic is strongly sequestered in the sediments rather than surface-adsorbed or associated with easily dissolved phases, which is consistent with the presence of small particles.…”
Section: Xasmentioning
confidence: 99%
“…No sulfide phases, either arsenic or iron, were detectable in bulk sediments with powder XRD (36). Sequential extraction of arsenic and iron from sediments using an extraction scheme optimized for arsenic (42) showed that arsenic is not dominantly associated with easily exchanged sorption sites or with reducible iron (36). This finding indicates that much of the arsenic is strongly sequestered in the sediments rather than surface-adsorbed or associated with easily dissolved phases, which is consistent with the presence of small particles.…”
Section: Xasmentioning
confidence: 99%
“…Previous studies have shown that this method extracts As from Fe oxides, metal sulfides, and As sulfides. 53,54 Reductive extractions leached 0.9-1.1 nanomoles As per gram of sediment dry weight ͑nmol/g͒ from the Ͻ2 mm sizefraction of sediments collected adjacent to the tracer test site and from the Ͻ1 mm size-fraction of a composite sample comprised of sediments from the uncontaminated zone ͑Table III͒. Preparation of this composite sample has been described elsewhere.…”
Section: Chemical Extractions Of Sedimentsmentioning
confidence: 99%
“…This means that the main leaching toxicity of As is caused by its residual fraction, which is different from the other metals that we investigated. A possible reason is that the residual fractions of As in all three fractionation procedures account for more than 97% of the total amount detected, and there are special SEPs developed for As (Keon et al, 2001) to account for its particularly reactive properties (Dold, 2003;Huang et al, 2007;Zhao et al, 2010;Zhao et al, 2009). Additionally, although the mean concentration of As detected in the TCLP leachate (4.46 ± 0.22 mg/L) was below the regulation limit, the concentration of As in the residues after each fraction for the three SEPs could exceed the regulation limit of 5 mg/L.…”
Section: Chemical Speciation Tests Combined With Tclpmentioning
confidence: 99%